`There are thousands of options out there': Exploring the Effectiveness of a Widening Participation Outreach Programme on Second-level Students' Educational Outcomes - Ní Chorcora, Eilís (Trinity College Dublin. School of Education. Discipline of Education, 2025)
This thesis explores the long-term impact of widening participation (WP) outreach on educational aspirations and post-school progression among students from marginalised backgrounds in Ireland. The research is grounded in national concerns about inequality in access to higher education, particularly for students attending schools designated as disadvantaged (DEIS) under the National Access Plan 2022 to 2025 (HEA, 2022). Despite ongoing policy efforts, there is limited empirical research on how WP interventions influence students' pathways over time. This study addresses that gap through an integrated, longitudinal research design that draws on both quantitative and qualitative data from students in Trinity Access Programme (TAP) partner secondary schools. The research is structured in three phases. Phase 1 comprises a systematic review of international literature, identifying the types of WP interventions studied and their impact on student aspirations and progression. Phase 2 uses secondary data from the TAP Longitudinal Study to examine the influence of outreach on students' goals, aspirations, and educational outcomes, while also exploring the role of contextual factors such as gender, ethnicity, and school type. Phase 3 involves primary qualitative interviews with former students from TAP partner schools, providing retrospective insights into how engagement in WP activities shaped their post-school trajectories. Findings show that sustained engagement with TAP outreach, particularly through multi-touchpoint pathways activities, was associated with increased future goals and aspirations and a higher likelihood of post-school progression. However, structural and contextual barriers continued to influence outcomes, suggesting that WP interventions alone cannot fully counteract systemic disadvantage. The thesis adopts a blended theoretical framework, drawing on Bourdieu's concepts of capital and Bronfenbrenner's ecological systems theory, to explore how social, relational, and structural factors interact over time. The study makes an original contribution by offering a multi-dimensional, contextually grounded understanding of WP effectiveness in the Irish context, with implications for policy, practice, and future research both nationally and internationally.
APPROVED
Keywords: secondary education; access; mentor; pathways; widening participation; progression; outreach; higher education